Estudos da competição entre laminina e ollgômeros Aβ pela ligação à PrPc e seus efeitos no ritmo circadiano - Luz, Marcio Henrique Mello da [UNIFESP] (2017)
Interaction between PrPC and Laminin (LN) promotes neuritogenesis via ERK1/2, while the interaction between PrPC and amyloid-beta oligomer (oAβ) triggers synaptic dysfunction via Fyn kinase, but both complexes use mGluR1 as co-receptor. The involvement of PrPC in these opposite functions suggests that PrPC-mGluR1 acts as a key complex in the regulation of synaptic activity. To better understand how this complex works, we evaluated the interference of oAβ on LN binding to PrPC. We also verified levels of these molecules in different circadian periods and after sleep deprivation (SD), as the synaptic activity oscillates along the sleep-wake cycle. Our results showed that the addition of oAβ reduced LN-PrPC binding, suggesting that these ligands can compete with each other. Regarding the expression levels, we observed a reduction of PrPC in sleep deprived animals, independent of circadian period. mGluR1 levels were increased during the activity period in control animals (CTa) compared to the rest period (CTr), however this variation was attenuated with SD. These results indicate that the signaling triggered by PrPC-mGluR1 might undergo circadian regulation through the alteration of mGluR1 levels, and that SD might impair this regulation. Moreover, the levels of amyloid-beta peptides (pAβ) were increased by SD in rest period (SDr) when compared with CTr group. This increase correlated with hyperphosphorylation of SRC kinases in SDr group and might have contributed to a higher deviation in NMDAR phosphorylation of the same group. Total NMDAR levels in CTr and CTa showed the same profile of mGluR1. Laminin levels did not varied between groups, however ERK1/2 phosphorylation presented subtle decrease in CTa group compared to CTr group, which was not observed in SD groups. These results suggest that ERK1/2 and NMDAR tend to function in an opposite way during the activity time in control animals. However, SD seems to attenuate the variation of ERK/12 activity and hyperactivate SRC kinases leading to a NMDAR deregulation.